The use of standard form of in Malaysian construction industry - Rosli, Nor Marina (2007)
Malaysian Construction Industry has never had any standard form of domestic subcontract. The contract between Main Contractor and Domestic Subcontractor are mainly based on non-standard form drafted by the Main Contractor. Many problems have arise from the use of these non-standard form of subcontract. In September 2006, the CIDB has published the Model Terms of Construction Contract for Subcontract Work with aim to reducing these problems. In relation to these, the objectives of the study are to determine the problems faced by domestic subcontractors associated with the use of non-standard form of domestic subcontract and also to determine whether the use of ‘Model Term’ will reduce the problems. The study shown that the problems faced by domestic subcontractor due to the non-standard form are problem with payment clause, termination clause, variation and also arbitration. The most frequently problem is problems related with payment clause. Most of the disputes arose because of lack of term and the parties are not fully understand the terms. The study also shows that the ‘Model Term’ will be able to reduce the problems. For example the payment clause is clearly stated all the right, obligation and duties of the parties. By using the plain English also can help the parties understand the contract they had entered.